Evaluation of the random amplified polymorphic DNA technique for the epidemiological investigation of streptococcus pneumoniae outbreaks. - Friedland, Hillel David (My University, 1994)
The emergence of strains of S. pneumoniae resistant to penicillin and to other antibiotics, and the spread of that resistance over the world, have become major concerns and increase the need for epidemiological surveillance. The following typing methods have been used to detect strain variability in pneumococci: Serotyping, antibiotic susceptibility profiles, multilocus enzyme electrophoresis (MLEE), penicillin-binding protein (PBP) profiles, pulse-field gel electrophoresis (pFGE), and ribotyping. Serotyping, antibiograms, and MLEE only detect phenotypic variability. PBP gene profiles, PFGE, and ribotyping detect genotypic differences but these techniques are labour intensive and time consuming. Random amplified polymorphic DNA (RAPD) is a new technique that bas proved useful for typing bacteria, fungi, and parasites, but has not been. studied using pneumococci. Unlike conventional polymerase chain reaction (peR), RAPD utilizes single, short primers, usually 10 oligonucleotides in length. As the primer is short and low astringency annealing temperatures are used, there will be many complimentary sites scattered randomly throughout a bacterium's genome, When such sites occur a few hundred base pairs away from each other and on opposite DNA strands, the enclosed region can be amplified by peR This results in numerous discrete target fragments which can be separated by agarose-gel electrophoresis and ethidium bromide staining. RAPD requires no sequence information and it scans the whole genome rather than relying on hypervariability within one specific gene. The aims of this study were: to determine strain variability using RAPD, to determine the reproducibility ofRAPD, and to demonstrate intercontinental spread of a multiresistant pneumococcal strain. The following strains were evaluated: a) 10 strains from a day-care centre (DCC), the index case being a 3 year old girl 'with otitis media. An aunt from Spain had recently been staying with the family. The other strains were isolated from class mates and siblings of the index case.; b) 18 clinical isolates from Seoul, Korea; and c) 11 epidemiologically unrelated isolates from South Africa, including the reference strain, R6. Two DNA extraction methods were used. The first involving lysis with sodmm-dodecyl-sulphaze and proteinase K. Proteins were removed with phenol-chloroform, and the DNA precipitated with ethanol. The second method involved incubating the cells at 95 0C for 15 microlitres, followed by centrifugation. 2 microlitres of the supernatant was then used for each PCR reaction, Three primers were evaluated. After 01uimisation of the RAPDreaction for pneumococci, the final peR mixtures per 50 ul was: primer (4 plY1), template (0.5 ng), nuc1eotides (300 pMeach), magnesium (4 mM~, and Taq polymerase (2 U). 35 cycles were used with an annealing temperature of 35'C. Both DNA extraction methods: gave reproducible results but were not comparable to each other. All 10 strains from the DCC gave the same banding pattern as the Spanish done for all 3 primers. 7 of the Korean strains gave the same banding pattern as the Spanish clone using the first two primers, however one strain showed an additional band using the third primer. Of the remaining 22 strains, 21 different banding patterns were obtained. This study has shown that RAPD is a simple and rapid technique that can distinguish strain variation among pneumococci. The reproducibility is excellent within the same laboratory. Finally using RAPD. this study identified a Spanish multiresistant 23F clone in South Africa and Korea.
A dissertation submitted to the Faculty of Medicine, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Medicine.
Keywords: Pneumococcal Infections epidemiology.; Steptococcus Pneumoniae epidemiology.; Bacterial Typing Techniques.